(untitled) (Global Journal of Human-Social Science, 2019)
Nigeria has been experiencing a high unemployment rate over the years The main objective of this paper is to investigate the effects of some macroeconomic variables such as Gross Domestic Product Treasury bill and Inflation rate on unemployment rate in Nigeria over the period 2006Q1-2018Q4 The long-run and short-run impacts of the variables were analyzed using the bound testing co-integration The result shows there is a long-run relationship among the variables The dynamic error correction was carried out and the long-run and short-run coefficients were extracted using the ARDL model The result shows that the Gross Domestic Product has a positive significance on unemployment in the long run However in the short-run only GDP contribute significantly to the unemployment rate The Granger non-causality shows that Treasury bills do not cause Gross Domestic Product There is unilateral causality from Treasury bill to the unemployment rate and inflation rate